Cellular and genetic control of antibody responses in vitro. III. Immune response gene regulation of accessory cell function - Singer, A (The Rockefeller University Press, 1978)
The possibility was investigated that Ir genes regulate the function of cells other than T or B cells in the primary IgM responses to the synthetic antigens trinitrophenylated poly-L-(Tyr,Glu)-poly-D,L-Ala--poly-L-Lys [TNP-(T,G)-A--L]and trinitrophenylated poly-,-(His,Glu)-poly-D, L-Ala--poly-L-Lys [TNP-(H,G)-A--L]. The primary responses of (B10 × B10.A)F(1) spleen cells to both antigens were abrogated by Sephadex G-10 passage, and restored by the addition of spleen adherent cells. The cell type in the spleen adherent cell population active in reconstituting the responses to TNP-(T,G)-A--L and TNP-(H,G)-A--L was a non-T, non-B, radiation-resistant, glass-adherent spleen cell. The responses of Sephadex G-10-passed (responder x nonresponder)F(1) spleen cells to TNP-(T,G)-A--L or TNP-(H,G)-A--L were reconstituted by spleen adherent cells from only responder strains. Spleen adherent cells from F(1) mice reconstituted the responses to both antigens. Spleen adherent cells from each of the strains tested reconstituted the non- Ir gene-controlled response to a third antigen, TNP-keyhole limpet hemocyanin. The inability of spleen adherent cells from nonresponder strains to reconstitute the responses to either TNP-(T,G)-A--L or TNP-(H,G)-A--L was not a result of active suppression induced by the presence of nonresponder adherent cells, since a mixture of responder and nonresponder spleen adherent cells reconstituted the responses to both antigens. The use of spleen adherent cells from recombinant strains demonstrated that the autosomal dominant genes controlling the ability of spleen adherent cells to function as accessory cells in the responses to TNP-(T,G)-A--L and TNP-(H,G)-A--L are located in the K or I-A regions of the responder H-2 complex, the same region(s) of H-2 as the Ir genes controlling overall in vitro and in vivo responsiveness to these antigens.